PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PUSKESMAS MADANDAN KECAMATAN RANTETAYO KABUPATEN TANA TORAJA - Patadungan, Ellyn; -, Marniati (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to determine the influence of work discipline, work environment, and work motivation on the performance of employees at Madandan Health Center, Rantetayo Subdistrict, Tana Toraja Regency. The research data were obtained by using questionnaires and documentation from the employees of Madandan Health Center, Rantetayo City, Tana Toraja Regency. The research method used in this study is quantitative research with a sample size of 36 people. The data analysis technique used in this study is multiple linear regression analysis with statistical calculation tools using SPSS version 25.0.The results of the study show that the work discipline variable has a significant influence on the performance (Y) of employees at Madandan Health Center, Rantetayo Subdistrict, Tana Toraja, with a value of0.048>0.05 and a t-value of 1.840<t-table 2.036. The work environmentvariable has a significant influence on performance (Y) with a value of 0.047<0.05 and a t-value of 2.065>t-table 2.036. The work motivation variable has a significant influence on performance (Y) with a value of 0.011<0.05 and a t-value of 2.0711>t-table 2.036. Work discipline, work environment, and work motivation variables simultaneously have a significant influence on the performance (Y) of employees at Madandan Health Center, Rantetayo City, Tana Toraja, with an F-value of 49.595 (>2.90).